Analysis of the Influence of Banking Risk on Bank Financial Stability: A Case Study of KBMI 4 Banks - Maulida, Rosa Arin; Munawar Ismail (Contemporary Studies in Economic, Finance and Banking, 2025)
This study aims to analyze the effect of banking risks, consisting of Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR), and Capital Adequacy Ratio (CAR), as well as the control variables Inflation, BI Rate, and GDP, on the financial stability of banks in the KBMI 4 group during the period 2012–2023. The data used are secondary data obtained from the annual financial reports of each bank, analyzed using panel data regression. The results show that NPL, CAR, and the BI Rate have a significant effect on banking stability, while LDR, inflation, and GDP do not. These findings indicate that banking stability is more strongly influenced by internal bank factors than by macroeconomic indicators. The results of this study are expected to serve as a reference for bank management in strengthening risk management and maintaining financial system stability.